Financial and nonfinancial profitability across time and frequencies - Ivan Mendieta-Mu\~noz; Daniel Ossa (The University of Utah, Department of Economics, 2022)
We contribute to the study of the conceptualization and measurement of the rate of profit of the financial and nonfinancial sectors. We assemble a new data set for the US economy to construct measures of the profit rate for each sector: the return on equity, the return on assets, and the shareholder's dividend yield. We study how the periodic components of the measures of profitability in each sector have changed over time, how these have been correlated at different frequencies, and what has been the evolution of such correlations. We find that the dominant correlation between the measures of profitability across sectors is located at business cycle frequencies, and that there has been a shift in the lead-lag relationship between financial and nonfinancial profitability: from 1970 to the mid-1990s, profitability in the nonfinancial sector led profitability in the financial sector; while since the mid-1990s the latter has led the former.
Keywords: B50; C32; E11; E32; G20; 330; profitability; financial corporations; nonfinancial corporations; business cycles; financialization